Peran Daya Juang Bagi Self-Regulated Learning Siswa SMA - Enasely Mega Wenyi Rohi; Yuzarion Yuzarion; Nurul Hidayah (Faculty of Ushuluddin and Humanities, 2021)
Self-regulated learning plays an essential role in achieving better academic achievement goals. This study aims to empirically examine how adversity quotient predicts self-regulated learning in senior high school students in Betun East Nusa Tenggara using a linear regression analysis technique of 120 participants selected based on purposive sampling. Measurements were made using 22 items of the adversity quotient scale (Cronbach’s α = 0.83) and 21 items of the self-regulated learning scale (Cronbach’s α = 0.95). The results showed a regression coefficient (t = 5.237) with a significance level p = 0.000 (p < 0.01), which mean that the adversity quotient can predict the self-regulated learning of senior high school students with an effective contribution of 21.5 per cent